Complex Terahertz and Direct Current Inverse Spin Hall Effect in YIG/Cu1-xIrx Bilayers Across a Wide Concentration Range - Cramer, Joel; Seifer, Tom; Kronenberg, Alexander; Fuhrmann, Felix; Jakob, Gerhard; Jourdan, Martin; Kampfrath, Tobias; Klaeui, Mathias (Nano Letters, 2018)
We measure the inverse spin Hall effect of Cu1-xIrx thin films on yttrium iron garnet over a wide range of Ir concentrations (0.05 ≤ x ≤ 0.7). Spin currents are triggered through the spin Seebeck effect, either by a continuous (dc) temperature gradient or by ultrafast optical heating of the metal layer. The spin Hall current is detected by electrical contacts or measurement of the emitted terahertz radiation. With both approaches, we reveal the same Ir concentration dependence that follows a novel complex, nonmonotonous behavior as compared to previous studies. For small Ir concentrations a signal minimum is observed, whereas a pronounced maximum appears near the equiatomic composition. We identify this behavior as originating from the interplay of different spin Hall mechanisms as well as a concentration-dependent variation of the integrated spin current density in Cu1-xIrx. The coinciding results obtained for dc and ultrafast stimuli provide further support that the spin Seebeck effect extends to terahertz frequencies, thus enabling a transfer of established spintronic measurement schemes into the terahertz regime. Our findings also show that the studied material allows for efficient spin-to-charge conversion even on ultrafast time scales.
CRIS-Team Scopus Importer:2023-03-27
Keywords: alloy; Spin Hall effect; spin Seebeck effect; terahertz emission; ultrafast spin currents